2020
DOI: 10.3390/ani10091631
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Studies of Rumen-Protected Microencapsulated Supplement Comprising Linseed Oil, Vitamin E, Rosemary Extract, and Hydrogenated Palm Oil on Rumen Fermentation, Physiological Profile, Milk Yield, and Milk Composition in Dairy Cows

Abstract: The aim of the present study was to evaluate the effects of adding dietary rumen-protected microencapsulated supplements into the ruminal fluid on the milk fat compositions of dairy cows. These supplements comprised linseed oil, vitamin E, rosemary extract, and hydrogenated palm oil (MO; Microtinic® Omega, Vetagro S.p.A, Reggio Emilia, Italy). For in vitro ruminal fermentation, Holstein–Friesian dairy cows each equipped with a rumen cannula were used to collect ruminal fluid. Different amounts (0%, 1%, 2%, 3%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…To the best of our knowledge, this study is the first of its type to show the comparison between the ruminal stability of free and microencapsulated forms of different essential oil products containing either a single essential oil or a blend of different essential oils (cinnamaldehyde, thymol, and eugenol), vitamins, or pro-vitamins. Kim et al [ 34 ], in a recent in vitro study, reported a high protection effect (99%) from rumen microbes for linseed oil coated with hydrogenated palm oil after 8 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first of its type to show the comparison between the ruminal stability of free and microencapsulated forms of different essential oil products containing either a single essential oil or a blend of different essential oils (cinnamaldehyde, thymol, and eugenol), vitamins, or pro-vitamins. Kim et al [ 34 ], in a recent in vitro study, reported a high protection effect (99%) from rumen microbes for linseed oil coated with hydrogenated palm oil after 8 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Microencapsulation is an emerging technology that is commonly used nowadays in human and animal nutrition for the preparation of stable products (vitamins, minerals, (polyunsaturated) fatty acids, and so on) [ 34 ]. Many studies have been conducted in the past on encapsulated EOs using different kinds of matrices to obtain the desired stability and site-specific, slow release of the products; e.g., microencapsulation with a lipid matrix is the most frequently used method for effective delivery of the product to the small intestine [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ingredients of the rumen-protected microencapsulated fatty acid from linseed oil (MO) were linseed oil (35%), vitamin E (0.5%), rosemary extract (0.3%), and hydrogenated palm oil (64.2%). The main components of the MO were crude fat (95%) and ash (5%) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were dried for 10 min and then further dried in a dry oven for 48 h at 60 °C before weighing. The levels of NDF and ADF digestibility were calculated based on the following equations [ 15 , 18 ]: NDF, ADF (%) = [dried residue − (filter bag weight × C)]/sample weight × 100. Correction (C) = dried blank bag weight/original blank bag weight.…”
Section: Methodsmentioning
confidence: 99%
“…Different strategies can be performed to increase the quality of animal diets, such as the use of coagulants [31]. In recent years there has been an increase in the studies about microencapsulation of organic compounds in order to improve the quality of animal diets [32,33,34], because protein protection is important. The choice of the encapsulating agent is performed according to the pH of four different ruminants' stomachs.…”
Section: Discussionmentioning
confidence: 99%